Introduction to Fractional-Order Control: A Practical Laboratory Approach. Issue 17 (2022) - Thomson, Dean; Padula, Fabrizio
Abstract: In this paper we propose the use of a temperature control problem as a method to introduce fractional modeling and control to students. The control problem is based on a simple laboratory setup: a heated aluminum rod that can be conveniently modeled from first principles by using fractional systems. The construction of the experiment only requires cheap components and can be easily replicated. Once a model is obtained, the student can control the temperature of the rod by using different control algorithms, fractional and integer, thus experiencing first-hand the benefits of fractional control and, more in general, exploring advanced control paradigms.